ДЕПРЕССИИ СНЕГОВЫХ ГРАНИЦ ПЛЕЙСТОЦЕНОВЫХ ОЛЕДЕНЕНИЙ ВОСТОЧНОГО ЗАБАЙКАЛЬЯ - Еникеев Ф.И. (My University, 2006)
The localization of the climatic and orographic snowlines during the Late Pleistocene glaciations was determined for the southern part of the East Siberia: Vitim-Olekma watershed and Eastern Transbaikalia. The deformation of the snowlines depends on global, regional, and local agents. Depression of the chionosphere reached 1400 m in the Sar-tan Ice Age, 1600 m - in the Muruktin, 1800 m - in the Tas stages, and more than 1900 - in the Samarovo Ice Age.
Keywords: 551.435.4(-925.16); Кайнозой::Четвертичная::Плейстоцен